A Case Report and Literature Review of Pseudo-TORCH Syndrome Type 2 (PTORCH2) - Rami A. Misk; Lama Qawasme; Fawzy M. Abunejma; Bahaa Ibrahim Abu Rahma; Ehab Mohammad Abuawwad; Raja Imad Abu Iram; Abdulrahman Hussein Karaki; Tareq Z. Alzughayyar; Jihad Samer Zalloum (Case Reports in Pediatrics)
A pseudo-TORCH syndrome is a rare autosomal recessive disease characterized by intracranial calcification and microcephaly, leading to spasticity and seizures, but the serology of TORCH infection is negative. We present a 4-day-old female patient with jaundice, abnormal movement, and convulsions who was found to be homozygous for the missense USP18 gene mutation that causes pseudo-TORCH syndrome 2 (PTORCH2). The patient was managed with conservative measures.